(untitled) (Bangladesh Heart Journal, 2016)
Cor triatriatum dextrum is an exceptionally rare congenital heart disease, in which the right atrium is partitioned into two chambers by a membrane to form a triatrial heart. It is caused by persistence of the right valve of sinus venosus. The aim of presenting this case is to develop awareness regarding cor triatriatum dextrum , though a rare case, can be present and may contribute to right heart failure and 2D-echocardiography is an important tool in making early and accurate diagnosis. We are reporting a case of an elderly Bangladeshi male presented with the features of mitral stenosis with pulmonary hypertension with CCF with respiratory tract infection, where cor triatriatum dextrum with an atrial septal defect was an incidental finding on routine echocardiographic assessment. Bangladesh Heart Journal 2016; 31(1) : 37-40